SUBTITLING STRATEGIES FOR TRANSLATING KOREAN TERMS OF ADDRESS INTO INDONESIAN - Lestari, Annisa Puji; Usmi, Usmi (Multikultura, 2026)
This study examines the subtitling strategies used in translating Korean terms of address into Indonesian, with a focus on how sociocultural meanings embedded in Korean address systems are conveyed in the target language. Employing a descriptive qualitative approach, the study analyses a corpus of dialogue excerpts taken from two Korean drama series. The findings identify seven categories of address terms: proper names, occupational titles, kinship terms, common nouns, attention-getters, pronouns, and child name-derived forms. Proper names are the most frequent category, followed by occupational titles, kinship terms, common nouns, and attention-getters, whereas pronouns and child name-based forms occur less frequently. This distribution reflects the Korean sociolinguistic preference for personalized and hierarchical forms of address that signal respect, familiarity, and social harmony. The analysis reveals six main subtitling strategies: borrowing, substitution, literal translation, explicitation, omission, and compensation. The results indicate that translating Korean terms of address requires sensitivity to sociocultural context and audiovisual constraints. These findings highlight the importance of context-sensitive decision-making in achieving pragmatic and cultural equivalence in audiovisual translation.